Concentration of wealth and income in post-pandemic Latin America: Measurement, results, and perspective - Germán Alarco Tosoni (economic sociology. perspectives and conversations, 2023)
High inequality of wealth and income (or its concentration) is nowadays an international concern, although in many Latin American countries the only concern is to reduce poverty due to a vision associated with the trickle-down economy (Roberts 2022). From the neoliberal perspective and from that of the groups of economic power, the problem of high inequality is not very relevant.
Keywords: 300